Bacterial Isolates in a Neonatal Intensive Care Unit-A Rural Perspective - Deepali Abhijit Ambike; Sandhya Vishal Haribhakta; Simran Cassem Rajabally; Nayanika Sanjiv Bhatia (JCDR Research and Publications Pvt. Ltd., 2019)
Introduction: Bacterial sepsis is one of the most common causes of mortality and morbidity in neonates. The spectrum of bacteria that cause neonatal sepsis varies and antibiotic resistance is an increasing problem for these bacteria. Aim: 1) To study the bacteriological profile in the neonates admitted in the Neonatal Intensive Care Unit (NICU) of a tertiary care teaching hospital. 2) To determine the antibiotic sensitivity pattern of the same so that appropriate antibiotics can be chosen to improve the treatment and asepsis. Materials and Methods: This was a retrospective observational study which was conducted in the NICU of a tertiary teaching hospital. All symptomatic neonates up to 28 days old admitted in NICU were included in this study. A total of 118 samples were sent for cultures. The data was obtained from the Neonatal ICU registers, Medical Department Records and Microbiology laboratory records. Results: In this study, 118 neonates were considered and depending upon the inclusion criteria those having neonatal sepsis and were admitted to the NICU were taken. The risk of having growth in preterm neonates is 2.27 times more than that in full term neonates. Prevalence of Microbial growth was highest in neonates who were less than 2 kg in birth weight i.e. very low birth weight babies. Microbial growth in neonates admitted within 3 days of life was 1.273 times more than that in neonates who were admitted after 3 days of life. Positive co-relation was seen between microbial growth and who stayed in the hospital for more than seven days. Out of 118 isolates, 80 had no growth, 13 showed MRSA positive, 9 were positive for Staphylococci, 8 were for Klebsiella, 3 Gram negative bacilli, 2 Citrobacter and 1 remaining. Conclusion: In view of the changing spectrum of the causative agents of neonatal septicaemia and antibiotic sensitivity and resistance pattern from time to time, a positive blood culture and the antibiotic sensitivity and resistance pattern testing of the isolates are the best guide to the antimicrobial therapy which would be beneficial to the best outcome of the disease.